Nas Electra Enterprise / Sharifah Azlina Syed Ahmad ... [et al.] - Seman, Noraini; Syed Ahmad, Sharifah Azlina; Abdullah Suhaimi, Afiza; Zakaria, Suriati; Abu Bakr Saleh, Saber (2004)
Nas Electra Enterprise provides a manufacturing of product, which is filtered water. Nas Drinking water and it will be bottled for 500ml. This water is consumable to all kind of ages just like the other filtered water. Besides, the price will be a slighty higher than other advantages offered. The address of our factory is Taman Sena Indah Persiaran, Jubli Emas, Kangar Perlis.